Utilization of palm oil mill effluent as new media for cellulase enzyme production - Alam, Md. Zahangir; Abdul Karim, Mohamed Ismail; Hamisan, Ahmad Fadhlan (2006)
A laboratory-scale cellulase production using palm oil mill effluent (POME) was carried out by Trichoderma harzianum in liquid state bioconversion (LSB). The optimum process conditions such as temperature, concentration of POME and co-substrate (wheat flour), pH, agitation rate and inoculum size obtained from previous study were used. Under these conditions, cellulase activity reached 13.2 FPU/ml after four days of fermentation. This study also involved the biodegradation of POME through the removal of chemical oxygen demand (COD) and reducing sugar. The maximum COD removal was 70% after 7 days of treatment. The product yields and its productivity were determined in order to evaluate the bioconversion process in LSB. The pH was measured in the entire fermentation process.